Nonlinear control and parametric uncertainties of flexible-joint robots - Lima, Jeferson J.; Ribeiro, Mauricio A.; Santos, Max M. D.; Janzen, Frederic C.; Balthazar, Jose M. [UNESP]; Tusset, Angelo M. (Springer Nature, 2024)
This study examines the relationship between the nonlinear behavior of the flexible joints of a fourth-degree-of-freedom robot and the controllability and parametric uncertainties of the system. The initial section of the paper presents the dynamic modeling of the robot and the proposed control strategies. This is followed by a parametric sensitivity analysis, which defines the optimal control strategy to be applied. Finally, the configuration of the experimental robot with flexible joints is presented. The SDRE and LQR strategies are related in the study, both in discrete mode and intended for use in the control unit. The final phase of the study involved the presentation of the results obtained when the robot was controlled using flexible joints. The findings demonstrated a positive outcome for the SDRE control strategy.
Keywords: Flexible-joint robots; LQR control; Parametric uncertainties; SDRE control